Domestic Violence and Extremism among the Young: A Field Study in the Madain Region (Journal Of Educational and Psychological Researches, 2023)
Abstract Young people represent the power and cornerstone of societies and their superiority is linked to their well-being. Their empowerment is as essential as the heart to the body, if it is corrupt, then the whole body is corrupt, and vice versa. The exposure to extremism and pressure from their families leads to violent acts and crimes for obtaining money through unknown organized bodies. This will drive them to fail in their life in an attempt to fulfill their most basic needs, which they have been deprived of by their families, the government, and other institutions. Therefore, governments should provide job opportunities for young people and provide entertainment centers, sports clubs, and family education centers that raise awareness of staying away from domestic violence and reduce family pressure on young people. Besides, governmental institutions should assist young people to achieve their ambitions, foster their talents, avail them in the decision-making process, and put them in the right place instead of stumbling into extremism, evil, and crime. The whole country and its society could be the target point of the young to reflect their extremism and deviation in countless ways. Crime, vice, and extremism, which have multiple sources and types, are spreading in society because of family breakdown, violence, lack of economic returns, and limited scientific level, in addition to the social environment  in which young people live. The findings of the study revealed that 95% of young people are exposed to extremism due to their continuing differences and permanent conflicts with their families. Also, in recent years, parents are preoccupied with poor living conditions and similar matters, resulting in neglecting their children who suffer pressure that leads them to perform extremism with other groups.